Impact of SiN passivation film stress on electroluminescence characteristics of AlGaN/GaN high-electron-mobility transistors. (2nd September 2021) - Ma, Qiang; Urano, Shiyo; Ando, Yuji; Tanaka, Atsushi; Wakejima, Akio
Abstract: This letter reports an impact of SiN film stress on electroluminescence (EL) of AlGaN/GaN HEMTs. The EL color of HEMTs turned from high-intensity white to low-intensity red, as the SiN film stress was increased from −24.2 (compressive) to +11.5 MPa (tensile). The weak reddish EL from the HEMT with a film stress of +11.5 MPa turned bright whitish when a drain-to-source voltage ( V ds ) was increased. A transient I d response after biasing stress revealed that severe current collapse emerged in the HEMT with a film stress of −24.2 MPa. In addition, the current collapse in HEMTs increased with the increased V ds .